2022
DOI: 10.1021/acs.energyfuels.2c02672
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Effect of Co3O4 Nanooctahedron in Boosting Oxygen Reduction and Oxygen Evolution Reactions

Abstract: We report a controllable synthesis of Co 3 O 4 nanooctahedron anchored on Vulcan XC 72R (Oct-Co 3 O 4 /C) to explore the crystal symmetry effects on the bifunctional electrocatalysis of oxygen reduction and oxygen evolution reaction (ORR/OER) in alkaline electrolyte. Systematic electrochemical measurements reveal that Oct-Co 3 O 4 /C exhibits remarkable ORR/OER activity with a higher ORR onset potential (E onset = 0.89 V), half-wave potential (E 1/2 = 0.68 V), large limiting current density (j = −6.38 mA cm −2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…The atomic percentages of Co 2+ and Co 3+ were determined from the deconvolution of Co 2p 1/2 and Co 2p 3/2 peaks. The Co 2+ /Co 3+ ratios for Sp-Co 3 O 4 /C and Co 3 O 4 /C are evaluated to be 3.2 and 2.3, respectively, suggesting the accumulation of a rich oxygen vacancy in both ECs …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The atomic percentages of Co 2+ and Co 3+ were determined from the deconvolution of Co 2p 1/2 and Co 2p 3/2 peaks. The Co 2+ /Co 3+ ratios for Sp-Co 3 O 4 /C and Co 3 O 4 /C are evaluated to be 3.2 and 2.3, respectively, suggesting the accumulation of a rich oxygen vacancy in both ECs …”
Section: Resultsmentioning
confidence: 98%
“…Hence, a high-performance bifunctional EC is required to diminish the ORR/OER overpotential as the usual kinetics of the oxygen reaction are incompetently faster. Noble metal-centered ECs, such as Pt-, Pd-, and Ru-based materials, are still the state-of-the-art ECs for ORR and OER today, but they account for the major fraction of the entire cost of an FC, limiting its commercialization. …”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, two single N species peaks in the spectrum XPS of N 1s ( Figure 2 e) correspond to graphitic N (400.6 eV) and pyridinic N (398.5 eV), respectively [ 40 ]. Figure 2 f shows four peaks corresponding to C–O (284.1 eV), C=C (284.5 eV), C–O (285.2 eV) and C=O (286.7 eV) [ 37 , 41 , 42 , 43 , 44 ]. The above results demonstrate that Co 3 O 4 /C−750 was successfully synthesized.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, they revealed that the active sites and the rate-limiting steps (RLS) for Co 3 O 4 (001) and (111) facets are different due to their different coordination environments and electronic structures, leading to a variation from octahedral to tetrahedral Co and from *OH and *O, respectively . Some other works also reported that the OER activities of Co 3 O 4 are different with the change of exposed planes [such as (001), (110), (111), and (012)]. , Besides, to explore the effects of crystal facets and compare their performance fairly, the other factors such as crystal structure and particle size are required to keep the same to minimize the impacts of other properties. , In addition to the crystal facets, the electronic structures, especially the surface electronic states of Co 3 O 4 , can be modulated by generating oxygen defects and further improve its electrocatalytic OER activity, which has been demonstrated extensively, whereas the aforementioned works on facet-dependent OER activity of Co 3 O 4 only focused on the effect of crystal facets but did not explore the influence of the incorporation of oxygen vacancy on the OER activity of Co 3 O 4 with different facets. Therefore, introducing oxygen vacancies into Co 3 O 4 with different exposed crystal facets would result in different impacts on the surface electronic structures, which may lead to the variation of the OER activity and electrocatalytic mechanism.…”
mentioning
confidence: 99%